The Purposes of Exit Exams in Higher Education: A Systematic Review Samson Worku Teshome - Teshome, Samson Worku (Indonesian Journal of Multidisciplinary Educational Research, 2025)
This systematic review examines the multifaceted role of exit exams in higher education, emphasizing their purposes, impacts, and implications for students and educational institutions. Analyzing a diverse range of studies from 2000 to 2024, the review reveals that exit exams serve both as tools for accountability and potential sources of inequity. While these assessments can enhance educational quality and student preparedness, they may disproportionately affect underrepresented students, leading to increased stress and anxiety. The findings indicate that the pressure associated with exit exams can negatively impact student well-being, particularly for those who do not pass. Additionally, the review discusses the importance of aligning exit exams with curricular goals to ensure relevance and effectiveness. The necessity for inclusive assessment practices is highlighted, alongside robust support systems to aid all students in navigating these challenges. Recommendations include fostering collaboration among faculty, ongoing research into the effectiveness of exit exams, and advocating for equitable assessment policies. Ultimately, the review underscores the need for continuous dialogue on the role of exit exams to ensure they fulfill their intended purposes while promoting educational equity.